2011
DOI: 10.1371/journal.pone.0023564
|View full text |Cite
|
Sign up to set email alerts
|

FGF-2 Deficiency Does Not Influence FGF Ligand and Receptor Expression during Development of the Nigrostriatal System

Abstract: Secreted proteins of the fibroblast growth factor (FGF) family play important roles during development of various organ systems. A detailed knowledge of their temporal and spatial expression profiles, especially of closely related FGF family members, are essential to further identification of specific functions in distinct tissues. In the central nervous system dopaminergic neurons of the substantia nigra and their axonal projections into the striatum progressively degenerate in Parkinson's disease. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Thus, Fgfr1/Fgfr2-mediated regulation of myelin growth can be genetically uncoupled as a late aspect of oligodendrocyte differentiation, coinciding with a late temporal upregulation of FGFs and FGF-receptors in the postnatal CNS. An approximately fifteen-fold increase in the levels of FGF1 and a 2–4 fold increase in the levels of FGF2, FGF22 and FGF3 transcripts (Ratzka et al, 2011) and of FGF2 protein (Riva and Mocchetti, 1991) were reported in the adult spinal cord relative to their levels at birth. At the receptor level, Fgfr2 expression begins late in oligodendrocyte-lineage cells and Fgfr1 is upregulated upon oligodendrocyte terminal differentiation, concomitant with the expression of major myelin protein genes (Fortin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Fgfr1/Fgfr2-mediated regulation of myelin growth can be genetically uncoupled as a late aspect of oligodendrocyte differentiation, coinciding with a late temporal upregulation of FGFs and FGF-receptors in the postnatal CNS. An approximately fifteen-fold increase in the levels of FGF1 and a 2–4 fold increase in the levels of FGF2, FGF22 and FGF3 transcripts (Ratzka et al, 2011) and of FGF2 protein (Riva and Mocchetti, 1991) were reported in the adult spinal cord relative to their levels at birth. At the receptor level, Fgfr2 expression begins late in oligodendrocyte-lineage cells and Fgfr1 is upregulated upon oligodendrocyte terminal differentiation, concomitant with the expression of major myelin protein genes (Fortin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and astrocytes produce several FGFs, prominently FGF1 and FGF2 which are expressed concomitantly with active myelination and are also identified in axons (Riva and Mocchetti, 1991; Elde et al, 1991; Matsuyama et al, 1992; Gómez-Pinilla et al, 1992; Nakamura et al, 1999; Ratzka et al, 2011; Becker-Catania et al, 2011). Oligodendrocyte-lineage cells express FGF-receptors in a developmentally regulated manner (Bansal et al, 1996; Fortin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Wildtype (WT, FGF-2 ϩ/ϩ ) and knockout (KO, FGF-2 Ϫ/Ϫ ) littermates were obtained by cross-breeding of heterozygous FGF-2 mice and genotyped by PCR as described previously (27). Dissected embryonic brains (E14.5) were fixed in 4% paraformaldehyde in PBS overnight at 4°C, cryoprotected overnight in 30% (w/w) sucrose, and embedded in Tissue Tec OTC compound (Sakura).…”
Section: Methodsmentioning
confidence: 99%
“…19 The plasmids encoding for enhanced green fluorescent protein (EGFP, pCAGGS-EGFP-Flag) and FGF-2 18kDa (pCAGGS-FGF-2 18kDa -Flag, NCBI GenBank accession NM_019305.2, 533-994 bp) have been previously described. 20,21 The pCAGGS-GDNF-Flag plasmid was constructed by polymerase chain reaction-based cloning of the rat GDNF coding sequence (NCBI GenBank accession NM_019139.1, 50-682 bp) using primers introducing MfeI and XbaI cloning sites and removing the stop codon. The in-frame cloned C-terminal 3× Flag tag of the pCAGGS-Flag vector backbone enabled convenient detection of all three proteins (EGFPFlag, FGF-2 18kDa -Flag, GDNF-Flag) with the same antibody (anti-Flag M2, F1804 Sigma-Aldrich, Seelze, Germany).…”
Section: Harvest and Culture Of Rat Bmscsmentioning
confidence: 99%